A terceirização por intermédio das cooperativas médicas como instrumento de ampliação das relações de trabalho: uma análise jurisprudencial - Dalazen, Tayane de Queiroz Cachoeira (2023)
The scope of this study is to analyze the requirements for the validity of outsourcing services through work cooperatives, with main attention to medical work cooperatives. For this purpose, five judgments of the Labor Court of Appeals from the 3rd Region were selected, two reforming decisions of trial courts that understood the characterization of a classic employment relationship between the parties, and three maintaining decisions that removed the recognition of the employment relationship, with the particularity of containing in their foundations the legitimacy of the institute. In search of a hermeneutic analysis of the subject, this research focused on the historical and panoramic context of the outsourcing of services, especially under the bias of outsourcing as an unstoppable socioeconomic phenomenon in Brazil, as well as in relation to cooperativism, specifically about cooperatives of work, collated in the constitutional orbit and, also, as a counterpoint, an analysis of cooperatives that do not have the due legitimacy. Thus, based on the theoretical and methodological aspects, within the framework of the five collated decisions, this research examined not only the validity of the institute, but also the benefits provided by outsourcing through medical work cooperatives, concerning to the professionals who militate in the area, but, above all, for society in general